The crystal structure of methyl 4-(3,4-dichlorophenyl)-2,7,7-trimethyl-5-oxo-1,4,5,6,7,8-hexahydroquinoline-3-carboxylate, C20H21Cl2NO3 - Wang Zhiqiang; Li Min (Zeitschrift für Kristallographie - New Crystal Structures, 2025)
C20H21Cl2NO3, orthorhombic, Pbca (no. 61), a = 14.938(3) Å, b = 13.224(3) Å, c = 18.753(4) Å, V = 3704.3(12) Å3, Z = 8, R gt (F) = 0.0462, wR ref (F 2) = 0.1435, T = 296(2) K.